Digital Mining Technology-Based Teaching Mode for Mining Engineering - Chen, Zhongqiang; Liu, Lang; Qi, Xueyuan; Geng, Junjun (International Journal of Emerging Technologies in Learning (iJET), 2016)
In this paper, the main problem in present mining engineering teaching was analyzed. Based on the analysis, the study of bringing digital mining technology into mining engineering teaching was presented. Furthermore, a new mining engineering teaching mode that includes mining knowledge demonstration, mining expertise building, mining environment modeling, and creative mining thought was also presented. In the teaching mode, 3D digital mining technology was used to model the mining environment. The modeled environment facilitated a systematic mining teaching system that helped students understand both mining concepts and mining operations. Thus, the instructor, student, and mining workers were essential to the teaching mode. The use of digital mining technology and relevant multimedia made mining teaching vivid and easy to be understood. Digitized primary data in mining engineering were readily and visually understood by students. Simulated 3D mining scenario generated with the data helped students understand theory and practice. Meanwhile, application of distant information technology helped mining workers in the abovementioned mining engineering teaching mode to be involved, thereby providing first-hand experience for classroom mining teaching. Hence, the digital mining based mining engineering teaching mode shows considerable promise in raising teaching effectiveness and efficiency.